The Study of Efficiency and Discipline on Shipment From Warehouse to Tanjung Priok Port - Firdaus, Miskul; Haroen, Zeinyta Azra; Saidah, Deslida (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2015)
Optimizing the use of land transport with the management of logistics and supply chain management of the warehouse to the port of Tanjung Priok can minimize cost, time, and quantity. It is hoped that the delivery of goods is faster, more focused and more precise. This research used descriptive quantitative and data is collected from secondary and primary data using SPSS software 27.00 version. Based on the three proposed research hypotheses, it is proven that the efficiency variable (X1) and discipline variable (X2) --- either individually or together --- have an influence to the shipment of goods from the warehouse in Tangerang to the Port of Tanjung Priok (Y). Keywords: efficiency, shipment discipline, logistics management, port.